Mercury-induced inflammation and autoimmunity - Pollard, K. Michael; Cauvi, David M.; Toomey, Christopher B.; Hultman, Per; Kono, Dwight H. (Biochimica et biophysica acta. General subjects, 2019)
Human exposure to mercury leads to a variety of pathologies involving numerous organ systems including the immune system. A paucity of epidemiological studies and suitable diagnostic criteria, however, has hampered collection of sufficient data to support a causative role for mercury in autoimmune diseases. Nevertheless, there is evidence that mercury exposure in humans is linked to markers of inflammation and autoimmunity. This is supported by experimental animal model studies, which convincingly demonstrate the biological plausibility of mercury as a factor in the pathogenesis of autoimmune disease. In this review, we focus on ability of mercury to elicit inflammatory and autoimmune responses in both humans and experimental animal models. Although subtle differences exist, the inflammatory and autoimmune responses elicited by mercury exposure in humans and experimental animal models show many similarities. Proinflammatory cytokine expression, lymphoproliferation, autoantibody production, and nephropathy are common outcomes. Animal studies have revealed significant strain dependent differences in inflammation and autoimmunity suggesting genetic regulation. This has been confirmed by the requirement for individual genes as well as genome wide association studies. Importantly, many of the genes required for mercury-induced inflammation and autoimmunity are also required for idiopathic systemic autoimmunity. A notable difference is that mercury-induced autoimmunity does not require type I IFN. This observation suggests that mercury-induced autoimmunity may arise by both common and specific pathways, thereby raising the possibility of devising criteria for environmentally associated autoimmunity. Mercury exposure likely contributes to the pathogenesis of autoimmunity. [Display omitted] •Mercury exposure is linked with inflammation, autoantibodies, and renal pathology.•Animal studies recapitulate the immune features of human exposure.•Differences in inflammation and autoimmunity are genetically regulated.•Required genes include those regulating innate and/or adaptive immunity.•Unlike idiopathic autoimmunity type I IFN is not required.